2023
DOI: 10.1039/d2ra08291h
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties and rare earth element diffusion behavior of hot-deformed nanocrystalline dual-main-phase Nd–Ce–Fe–B magnets

Abstract: To inhibit the magnetic dilution effect of Ce in Nd–Ce–Fe–B magnets, a dual-alloy method is employed to prepare hot-deformed dual-main-phase (DMP) magnets using mixed nanocrystalline Nd–Fe–B and Ce–Fe–B powders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It has been reported that, the coercivity temperature coefficient β for melt-spun Nd-Fe-B and Ce-Fe-B ribbons are generally about −0.30~−0.40%/K and −0.50~−0.60%/K [14,27,28]. The β values of HDed Nd-Fe-B and Ce-Fe-B magnets in 300-400 K are −0.570%/K and −0.530%/K [29]. Therefore, Y-Ho-Fe-B magnets are superior in terms of thermal stability.…”
Section: 3mentioning
confidence: 99%
“…It has been reported that, the coercivity temperature coefficient β for melt-spun Nd-Fe-B and Ce-Fe-B ribbons are generally about −0.30~−0.40%/K and −0.50~−0.60%/K [14,27,28]. The β values of HDed Nd-Fe-B and Ce-Fe-B magnets in 300-400 K are −0.570%/K and −0.530%/K [29]. Therefore, Y-Ho-Fe-B magnets are superior in terms of thermal stability.…”
Section: 3mentioning
confidence: 99%
“…From a strategic point of view, the partial substitution of the more critical neodymium (Nd) with Ce in FeNdB permanent magnets (with as much Ce as possible) is therefore interesting in terms of resource and economic efficiency and sustainability [14,15]. This applies equally to all types (sintered [14][15][16], melt-spun [15,[17][18][19], hot-deformed [15,[20][21][22][23]) of today's most powerful FeNdB magnets. However, there are significant differences between the Fe-Ce-B system and the Fe-Nd-B system, particularly with regard to intrinsic magnetic properties of the hard magnetic 14:2:1 phase, phase equilibria, and the resulting microstructures and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%